2017
DOI: 10.3390/su9040559
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Ozone and Cardiovascular and Respiratory Disease Mortalities Due to Ozone in Shenzhen

Abstract: Abstract:In order to explore the temporal-spatial patterns and possible health effects of ozone in Shenzhen, daily concentrations of ozone and the daily mortality caused by cardiovascular and respiratory diseases were collected. Using Geographic Information System (GIS) and SPSS, the spatial and temporal patterns of ozone in Shenzhen were illustrated. Using a generalized additive model (GAM), the associations between ozone and cardiovascular and respiratory diseases causing mortality were analyzed, adjusted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…In contrast, we found that men were more susceptible to the effects of O 3 on respiratory mortality than women. A research carried out in Shenzhen also found the similar result [ 55 ], which could be explained by the fact that pneumonia and bronchitis were more commonly observed in men who had a smoking history and different occupational exposures, which may exacerbate the impact of O 3 on respiratory mortality [ 56 ].…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, we found that men were more susceptible to the effects of O 3 on respiratory mortality than women. A research carried out in Shenzhen also found the similar result [ 55 ], which could be explained by the fact that pneumonia and bronchitis were more commonly observed in men who had a smoking history and different occupational exposures, which may exacerbate the impact of O 3 on respiratory mortality [ 56 ].…”
Section: Discussionmentioning
confidence: 68%
“…Our research also found that ozone in spring and autumn had an effect on non-accidental mortality but was not statistically signi cant. Research conducted in many regions of East Asia found that O 3 levels in different seasons have varying degrees of impact on non-accidental mortality [51]. This may be due to geographical heterogeneity [52].…”
Section: Resultsmentioning
confidence: 99%
“…The lag effects of each indicator of nitrogen oxides on cardiovascular mortalities were also examined. Our previous work suggested that the effects of confounding air pollutants were stable with a 3-day lag (Wang et al, 2017;Wu et al, 2016;Zhang et al, 2016). Therefore, this study selected 3 days to analyse the lag effects.…”
Section: Statistical Analysesmentioning
confidence: 99%